Effect of Government Expenditures and Banking Loan Distribution on the Performance of Human Resource Development in Papua Province - Lembang, Hendricus (International Journal of Social Science and Business, 2019)
The research aims to analyze government expenditure on capital spending and bank loan as well as to determine whether it has positive and significant effects on the Human Development Index (HDI) in Papua Province. The method is a quantitative study using a quantitive approach (deductive) to test the hypothesis and explain the causal relationship among panel variables (explanatory research). Data analysis techniques in the form of pooled data. Time series data were taken from 2005 to 2012 and the cross  section data consisting of 19 regioncies and 1 city in Papua Province. The research results about the local government expenditure indicate that 10 the capital expenditure has positive and significant direct effect on an increase in private investment, educational level, employment recruitment and HDI, 2) the bank consumer loan distribution has positive and significant effect on the labor absorption,  3) the private investment has positive but not significant impact on educational level; it has positive and direct significant impact in the labor absorption, 4) the level of education has positive and direct significant impact on the employment recruitment and HDI, 5) labor absorption has positive and direct significant impact in the HDI.